Dejavnost Utopije - Vogrinc, Jože (Monitor ISH, 2009)
The lecture to a non-scholarly audience is an adaptation of an unfinished research into More's Utopia as a source of early modern utopias and ideologies. It strives to disentangle the textual strategy of Utopia. It is argued that More's famous book should not be reduced to his intentions and neither to his catholic belief or his sympathy for a communist society. To be able to understand the fate of Utopia as "the first utopia" we should read it as a humanist literary text. It is a Menippean satire, shielded with compositional and rhetorical means. By placing its imagined society on a presumably existing island, it generates utopia as a modern genre. What is presented in utopia is represented as potentially real, as realiyable. Political objectives and effects of modern utopias are the result of a belief in their realiayability.
Keywords: More, Thomas, 1478-1535; More, Thomas: Utopija; utopija